Proces zarządzania rozwojem infrastruktury technicznej w gminie w świetle badań - Nowak, Magdalena (Management Process of the Technical Infrastructure Development in Commune - on the Example of Communes of Lodz Province, 2007)
Technical infrastructure is one of the main basis of the local social and economic growth. It implicates the level of life of the citizens and decides about the localization of private business in the area. Its development is the local government domain. Nevertheless effective management in this field depends on many factors - organizational, financial or legal. The objective of this paper is to present some analysis outputs concerning the above mentioned problem in communes of the Lodz prowince.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 667-678